Agrarian Conflict and Customary Land Rights: An Adat Law Perspective on Land Dispute Resolution - Loso Judijanto (Journal of Adat Recht, 2025)
Land disputes in Indonesia persist as a major issue, primarily arising from the conflict between the formal national legal system and the Indigenous legal traditions governing land ownership, particularly Adat Law. This research investigates agrarian conflicts, focusing on how traditional land rights (hak ulayat) often clash with the modern legal frameworks that dominate the national system. The study identifies the profound disconnect between state laws and the cultural practices of Indigenous communities, stressing the urgent need for a legal framework that honors both formal and customary law. Through the examination of current conflict cases, the research demonstrates that traditional conflict resolution methods rooted in Adat Law, with their emphasis on community consensus, offer a more sustainable and just approach compared to rigid state systems. The findings argue for the acknowledgment and legal incorporation of customary law in addressing land disputes, thereby protecting the land rights of Indigenous peoples. Furthermore, the study advocates for a transformation in national agrarian policies to establish a cohesive legal approach that respects and integrates both customary and formal legal systems, ultimately paving the way for a more inclusive and just agrarian reform process.